Metafizyka w filtrze neopozytywizmu. Śladem kontrowersji: Karl Popper - Koło Wiedeńskie - Pietruska-Madej, Elżbieta (Filozofia Nauki, 1996)
In Polish philosophical literature, especially didactic, a stereotype of Popper as a neopositivist is suprisingly stubborn. This stereotype does not help in understanding the relation between Popper and Vienna Circle, and the evolution of Popper's own views. Antimetaphysical bias of the neopositivists stands in evident contradiction to Popper's approach, who based his conceptual system on metaphysical ideas. In the article I qrgue that „late” Popper did not conctradict himself from the Vienna period. I show that „Logik der Forschung” is usually read through the neopositivistic filter, and that is why Popper's statements are so often misinterpreted.